Analiz urovnja sformirovannosti professional'nych umenij i navykov trenerov v processe obucenija v vuze - Zubova, E. A.; Zubov, S. M. (Vestnik sportivnoj nauki; Sports science bulletin, 2018)
The need for constant updating of knowledge in maintaining the required level of readiness to perform increasingly complex social and professional functions requires close attention to the quality of training, including in the sphere of physical culture. The problem of improving the quality of the training of trainers in the field of physical culture and sport is relevant in connection with dynamic ongoing process of modernization of universities. The development of sports high level sports result - one of the tasks of strengthening and development of society. This is largely determined by the preparedness of the athlete, which depends on technical, tactical, physical (General and special), moral and volitional training. The growth of sports skills is not possible without a coach. Is that the coach is the main incentive for achieving any result. From fitness trainer dependslargely on the level of achievement of the athlete.